Level of intention to use GIS among online journalism - Bayog, Katrina Coleen
Geographical Information System or GIS is a new technology being used by different international news organizations to provide a more comprehensive reporting for their consumers. GIS is a data visualization tool which maps out the news articles linked to where they have happened, providing a more sophisticated visual output. However, despite the potential of GIS in journalism and reporting, there has been a limited use of this system in local and national news reporting, both online and on print in the Philippines. This study looks into the level of intention to use GIS by local online newspaper journalists in online news reporting. Using a framework derived from the Technology Acceptance Model and the Unified Theory of Acceptance and Use of Technology, the researchers employ a non-experimental relational study design to determine which is the strongest predictor for intention to use GIS among the three constructs of UTAUT model ? Performance Expectancy, Effort Expectancy and Social Influence. Their findings show that PPI-member journalists in Western Visayas had a high intention to use GIS in their online news reporting. The researchers recommend, for future study, the employment of the ?actual use? construct of Technology Acceptance Model (TAM) and/or the Unified Theory of Acceptance and Use of Technology (UTAUT). They also encourage an experimental design with the controlled and uncontrolled variables in conducting the test. This can give an accurate comparative depiction of journalists who were exposed to the explainer video from those who were not exposed.